Does Information and Communication Technology Complement or Replace Social Travel among Young Adults?. Issue 1 (January 2015) - Delbosc, Alexa; Currie, Graham
Young adults are becoming less dependent on the car for travel. Increased use of information and communication technology (ICT) has been linked to this trend; this link suggests that ICT enables connection without wheels and thus less travel. This study tested that theory through a survey of young adults in Melbourne, Victoria, Australia. Two competing hypotheses were tested: (a) increased contact through ICT replaces–reduces in-person travel and (b) increased contact through ICT complements–increases in-person travel. The survey found that contact with friends was a high priority for young adults: 81% contacted friends daily through social media, 74% by phone, and 39% in person. A multinomial logistic regression tested associations between frequent in-person contact and several variables. Daily social media and telephone contact with friends was strongly associated with more frequent in-person contact. Daily social media use made someone 6.7 times more likely to have seen friends daily, while daily phone contact made someone 9.9 times more likely to have seen friends daily. The findings supported the complement–increase hypothesis (i.e., ICT use complements in-person contact rather than replaces it). Results are discussed and future research directions proposed.